Efficacy of Manipulative Games on Lower Basic Pupils' Academic Achievement in Mathematics in Plateau State, Nigeria - Ogunjimi, Mayowa Olurotimi; Aremu, Victoria Iyabo; Gyang, Raymond Pam; Abdulkareem, Taofeek Olarewaju; Dung, Stephen (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2024)
Manipulative games are designed to enhance experiential learning of Mathematics for kids in primary education. The subpar performance of primary school students in Mathematics has been attributed to the use of a teacher-centered educational method. This study investigated the efficacy of manipulative games on the arithmetic performance of lower basic pupils in Plateau State. This study utilized a 2X2X2 pre-test, post-test, control group non-equivalent quasi-experimental design. The study's population focus included all elementary schools with a solitary pupil, encompassing both public and private institutions. A multistage sampling method was utilized to choose a sample of 106 pupils. The experimental groups were administered the treatment package encompassing four mathematical themes. The experimental and control groups underwent pre-test and post-test evaluations using a validated Mathematics Achievement Test (MAT) that has a reliability coefficient of 0.81. The presented hypotheses were evaluated using Analysis of Covariance (ANCOVA) with a significance level of 0.05. The study's results demonstrated a significant effect of manipulative games on the academic performance of lower basic learners in Mathematics in Plateau State. The study concluded that manipulative games affect the mathematics ability of primary school kids, regardless of gender or kind of institution. The study recommended the incorporation of manipulative games into the basic school curriculum to enhance the teaching and learning of Mathematics.